Modern diagnostics of gastroesophageal reflx disease: actual progress and prospects - M. B. Scherbynina; T. M. Shevchenko; V. M. Hladun (Patologìâ)
According to modern concepts, gastroesophageal reflx disease (GERD) is referred to quasi-endogenous diseases. It is recognized that the underlying cause of the disease is the discoordination of the motor and evacuation function of the upper digestive tract, primarily the oesophagogastric transition as an antireflx barrier. The decrease in clearance of the оesophagus with time leads to a change in the structure of its mucosa in the form of Barrett’s oesophagus and cancer. From this perspective adequate treatment of GERD requires early detection. It is important to understand the possibilities of modern clinical and instrumental methods of diagnosing GERD in the everyday practice of gastroenterologists. The review presents the fidings of the American and Lyon consensus about GERD. It is shown that the criteria for GERD determining are specifi for each method of its diagnosics, so additional research may not always confim the diagnosis. The main methods of diagnosing GERD are the upper endoscopy, the 24-hour pH-metry monitoring. The latter is the gold standard for assessing the presence of gastro-оesophageal reflx. To make a decision before invasive antireflx procedures and surgery, high-resolution manometry (HRM) is recommended. Further studies are related to the use of three-dimensional high-resolution manometry (3D-HRM). HRM and 3D– HRM of the esophagus are high-tech methods for diagnosing the oesophageal motor function, with an encouraging prospect. However, consensus on GERD confimed there are no current limitations of available studies of the оesophagus and offr to look for new directions in diagnosis and treatment approaches. In this connection, it is interesting to analyze the sound signals of muscle fiers. The review presents data on the possibilities of modern clinical and instrumental methods for diagnosing GERD in the everyday practice of gastroenterologists and discussing a number of promising initiatives in this direction.